Parotid Gland Metastasis From Breast Cancer: A Case Report - Bob Andinata; Dewi Iriani; Adlina Karisyah (Indonesian Journal of Cancer, 2020)
Introduction: Breast cancer metastasis at the parotid gland is uncommon. There were only 21 cases reported until the recent year, and none of them came from Indonesia. The reports showed that breast cancer metastasis is more often found at the liver, lung, bone, and brain. Therefore, any masses found on the parotid are usually considered as a double primer.Case Presentation: We report a case of a woman, firstly diagnosed with luminal A stage IIA breast cancer at 39 years old. The patient had undergone breast-conserving therapy (BCT), followed by adjuvant hormonal therapy before being diagnosed with bone metastasis four years later. She also complained about a painful mass on her left upper neck. Ultrasonography and CT-scan resulted in insignificant abnormality. After a year with increasing painful mass, we performed FNAB. The result showed metastatic adenocarcinoma with a suspicious breast cancer origin. We did total parotidectomy with facial nerve preservation to alleviate the pain. Pathology results showed a confirmed diagnosis of breast cancer metastasis. The patient was given radiotherapy as local control and was scheduled to receive chemotherapy as systemic therapy.Conclusions: Parotid mass with a clinical symptom in the patient with the history of breast cancer should be evaluated firstly by imaging and may be followed by cytology or pathology evaluation to confirm whether it is primary or secondary malignancy. If the parotid metastasis from breast cancer is confirmed, we should consider adding systemic therapy after completing the local control.